A Study of Investors Awareness towards ETF in Comparison with Other Traditional Investment Options. - Balaji D Guttal; Avinashkumar; Arpita Purohit; Bhavana Koppad; Chetan Sankoji (Journal of Corporate Finance Management and Banking System ( JCFMBS) ISSN : 2799-1059, 2022)
The present study is conducted with the objective of assessing the awareness level of the investors. The success of ETF depends upon the awareness and confidence level of the investors. The investment pattern varies with age, education, gender, occupation. The study was conducted in Karnataka the study is based on primary data with a sample size of 87 respondents the study observed that awareness about ETF among the investors. It also observed no significant difference in the awareness level the investors belonging to different education background and gender. There is no significant difference in the awareness level about ETF Investment with respect to age, gender, qualification & occupation.